Gc-ms analysis of some bioactive constituents of mussaenda frondosa linn. - S.GOPALAKRISHNAN; E.VADIVEL (International Journal of Pharma and Bio Sciences, 2011)
Mussaenda frondosa is one of the medicinally important plants belonging to the family Rubiaceae, commonly known as ”Vellai ilai” in Tamil. Traditionally leaves are used in the treatment of jaundice, asthma, hyperacidity, ulcers, leprosy, diuretic, wound, swells, antimicrobial, diuretic activity, hypolipidemic effect, hepatoprotective activity, fever and cough. In the present study the ethanolic extract of Mussaenda frondosa has been subjected to GC-MS analysis. Twenty chemical constituents have been identified, The major chemical constituents are (-)-Quinic acid (32.87 %), 4-((1E)-3-Hydroxy-1-propenyl)-2-methoxyphenol (8.30%), Naphthalene, decahydro2-methoxy-(7.20 %). 1, 2, 3-Benzenetriol (7.70%),